Regionalisation and regionalism in world trade - Axel Borrmann; Georg Koopmann (Intereconomics, 1994)
The growing importance of regional integration, particularly in the Triad of Western Europe, North America and the Asia-Pacific region, is not always regarded as positive, but is also criticized because of the dangers involved for free world trade. What effects on world trade are to be expected? Can the new world trade order limit the possible risks?
Keywords: 330; International Trade